(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2023)
Background: Variations in morphology and metrical values of Gall Bladder (GB) is quite common. These variations are frequently observed during imaging and procedures like laparoscopy and cholecystectomy. The anatomical variation of GB is essential to clinician. Method: 48 adult cadavers were studied to evaluate the morphometric study of GB. The size and shape were classified with percentage. The length and breadth were measured with tailors tape. Results: 52.08% pear shaped, 10.4% flask shaped, 12.5% cylinder shaped, 6.25% hour glass shaped, 6.25% intra hepatic, 2.08% left GB, 2.08% double GB were studied. The mean length of GB was 6.80 (±1.42), 2.82 (±0.78) was mean breadth of GB, t test was 17.2 and p<0.01 Conclusion: The anatomic variations of GB and biliary tract are critical during surgical procedure. The present study will certainly help surgeon to carry out surgeries without causing morbidity and mortality. Moreover these variations will help the radiologist for proper reporting the diseases related to GB and biliary apparatus.